Recent updates on the recommendations for the management of ankylosing spondylitis: what and why?. (June 2013) - Schiotis, Ruxandra Elena; Calvo-Gutiérrez, Jerusalém; Salas, Adrian; Font-Ugalde, Pilar; Castro-Villegas, María del Carmen; Collantes-Estévez, Eduardo
Research in ankylosing spondylitis is a growing field. The recent publication of Assessment in SpondyloArthritis International Society classification criteria has permitted early diagnosis of axial and peripheral spondyloarthritis, which allows early therapeutic interventions. Ankylosing Spondylitis Disease Activity Score has been probed as a useful tool to measure disease activity. Treatment is based on physical therapy and NSAIDs. In refractory cases, the administration of anti-TNF drugs has set a new milestone, as it was shown to be highly effective in radiographic, as well as in nonradiographic, forms of the disease. New biological treatments are being investigated to add new therapeutic options to the armamentarium of the rheumatologist.